2021
DOI: 10.3389/fpsyg.2021.637436
|View full text |Cite
|
Sign up to set email alerts
|

Are Emotion Regulation Strategies Associated With Visual Attentional Breadth for Emotional Information in Youth?

Abstract: Attentional deployment is currently considered as one of the most central mechanisms in emotion regulation (ER) as it is assumed to be a crucial first step in the selection of emotional information. According to the broaden-and-build theory, positive emotions are associated with attentional broadening and negative emotions with attentional narrowing toward emotional information. Given that ER strategies relying on attentional deployment (i.e., rumination, cognitive reappraisal and distraction) have the possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…This attentional narrowing effect has been equally shown for positive and threatening stimuli (Álvarez-San Millán et al, 2022; Goodhew & Edwards, 2022). However, individual differences in emotion regulation might modulate this effect (Boelens et al, 2021). Further, a recent study (Gokce et al, 2021) has shown that positive affective pictures could increase WM capacity compared to neutral pictures, which could also be behind the increased performance for positive stimuli we observed.…”
Section: Discussionmentioning
confidence: 99%
“…This attentional narrowing effect has been equally shown for positive and threatening stimuli (Álvarez-San Millán et al, 2022; Goodhew & Edwards, 2022). However, individual differences in emotion regulation might modulate this effect (Boelens et al, 2021). Further, a recent study (Gokce et al, 2021) has shown that positive affective pictures could increase WM capacity compared to neutral pictures, which could also be behind the increased performance for positive stimuli we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Instead adaptive ER implies the flexible use of a range of ER strategies to meet contextual demands (Blanke et al, 2020). In line with this, previous work in adolescents has revealed that high trait levels of distraction resulted in more attentional narrowing (Boelens et al, 2021). Distraction is only seen as an adaptive strategy when it is flexibly used and combined with other strategies such as acceptance (Wolgast and Lundh, 2017).…”
Section: Figurementioning
confidence: 82%
“…For example, When Tai Chi is practiced, the practitioner is first asked to relax, to be calm and gentle, to leave all distractions behind, and to focus all attention on their breathing and senses, which is a kind of attention training. Attention deployment is now considered to be one of the core mechanisms in emotion regulation (Boelens et al, 2021) and a prior emotion regulation strategy that has an important impact on the generation, maintenance, or modification of emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is predicted that there is an association between emotional regulation (ER) and the visual attention breadth of emotional information (Fredrickson and Joiner, 2002). Similarly, there is a multifaceted relationship between distraction strategies in emotion regulation strategies and the visual attention breadth for emotional information (Boelens et al, 2021). Tai Chi practice makes individuals pay attention to body posture, action sequences, breathing, and strength at all times, allowing the individuals to increase attention breadth and improve their emotion regulation.…”
Section: Discussionmentioning
confidence: 99%